Universal structure motifs in biominerals: a lesson from nature for the efficient design of bioinspired functional materials. Issue 4 (6th August 2017) - Harris, Joe; Böhm, Corinna F.; Wolf, Stephan E.
Abstract : Biominerals are typically indispensable structures for their host organism in which they serve varying functions, such as mechanical support and protection, mineral storage, detoxification site, or as a sensor or optical guide. In this perspective article, we highlight the occurrence of both structural diversity and uniformity within these biogenic ceramics. For the first time, we demonstrate that the universality–diversity paradigm, which was initially introduced for proteins by Buehler et al . (Cranford & Buehler 2012 Biomateriomics ; Cranford et al. 2013 Adv. Mater. 25, 802–824 (doi:10.1002/adma.201202553 ); Ackbarow & Buehler 2008 J. Comput. Theor. Nanosci. 5, 1193–1204 (doi:10.1166/jctn.2008.001 ); Buehler & Yung 2009 Nat. Mater. 8, 175–188 (doi:10.1038/nmat2387)), is also valid in the realm of biomineralization. A nanogranular composite structure is shared by most biominerals which rests on a common, non-classical crystal growth mechanism. The nanogranular composite structure affects various properties of the macroscale biogenic ceramic, a phenomenon we attribute to emergence. Emergence, in turn, is typical for hierarchically organized materials. This is a clear call to renew comparative studies of even distantly related biomineralizing organisms to identify further universal design motifs and their associated emergent properties. Such universal motifs with emergent macro-scale properties may represent an unparalleled toolbox for the efficient design of bioinspired functional materials.